1977
DOI: 10.1007/bf00293656
|View full text |Cite
|
Sign up to set email alerts
|

Binding of mercury and selenium in subcellular fractions of rat liver and kidneys following separate and joint administration

Abstract: The distribution of mercury and selenium has been examined in subcellular fractions of rat liver and kidneys in prolonged exposure to HgCl2 and Na2SeO3 administered separately and simultaneously. The molar ratio of mercury and selenium concentrations in subcellular fractions of the organs examined varied considerably. Selenium displaced mercury from the soluble kidney fraction bound mainly with metallothionein to the nonhistone protein fraction of liver nuclei. The Hg-stimulated biosynthesis of metallothionein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(27 citation statements)
references
References 17 publications
3
24
0
Order By: Relevance
“…Apart from the soluble fraction in the kidneys, Environmental Health Perspectives (37,40,(51)(52)(53).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the soluble fraction in the kidneys, Environmental Health Perspectives (37,40,(51)(52)(53).…”
Section: Resultsmentioning
confidence: 99%
“…According to some authors, in the case of mercuric chloride the mechanism of the detoxifying action of selenium involves a decrease in the renal level of mercury, and therefore a diminution of the nephrotoxic effect (22,24,29,36), the effect of selenite depending on its concentration as well as on the time and kind of exposure (37)(38)(39)(40)(41)(42).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies indicate that the interaction effect of selenium and inorganic mercury is different and is characterized by a clear-cut translocation of mercury from low molecular to high molecular weight kidney proteins (24,26,27,64) already at equimolar concentrations of mercury and selenium (27). This phenomenon is accompanied by about a fivefold diminution of mercury concentration in the kidneys and inhibition of metallothionein biosynthesis (26,27,(64)(65)(66).…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of mercury in the liver and blood are significantly enhanced, but simultaneously the mercury content of the kidney is significantly reduced (21)(22)(23)(24). These changes are most pronounced when mercury and selenium are administered at at least equimolar doses (21-*Department of Toxicological Chemistry, Institute of Environmental Research and Bioanalysis, Medical Academy of L6dt, Narutowicza 120 A, 90-145 L6d&, Poland.…”
Section: Introductionmentioning
confidence: 99%
“…The mutual interaction between mercury and selenium differs from species to species (Cuvin-Aralar and Furness, 1991), mainly relying on their molar ratios (Komsta-Szumska and Chmielnicka, 1977;Cuvin-Aralar and Furness, 1991). Koeman et al (1973) first found a molar ratio of 1:1 between mercury and selenium in dolphin and seal that could significantly reduce toxic effects induced by the single pollutant.…”
Section: Introductionmentioning
confidence: 99%